2021
DOI: 10.17221/154/2020-pps
|View full text |Cite
|
Sign up to set email alerts
|

Residue and dissipation dynamic of spinetoram insecticide in pear fruits

Abstract: Cacopsylla pyri (Linnaeus, 1758) is the most significant and widespread pear pest. It attacks the pear only, causing direct and indirect damages. This study was conducted in order to evaluate the efficacy of insecticide spinetoram in the control of C. pyri. The experiment was set up according to EPPO methods, at the locality Kula (Republic of Serbia) in a pear orchard (Williams variety). Spinetoram (250 g/kg a.i., WG) was foliar applied in the amount of 0.3 kg/ha, during overlapping pest generations, when pear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…The recorded amount of terminal residues was lower than the prescribed MRL value (1 mg kg −1 ) of spinetoram in red bayberry [ 38 ]. Similar observations were found in various studies where spinetoram half-life values were reported as 1.29 d in cabbage, 1.95 d in pepper [ 39 ], 2.17 d in pear fruits [ 40 ], 2.6 d in tomato [ 41 ], 4.85 d in cauliflower [ 42 ] and 1.1 d in rice straw [ 16 ]. Faster dissipation of spinetoram from the plant surface may also be attributed to volatilization of the insecticide from the crop surface [ 41 ].…”
Section: Discussionsupporting
confidence: 90%
“…The recorded amount of terminal residues was lower than the prescribed MRL value (1 mg kg −1 ) of spinetoram in red bayberry [ 38 ]. Similar observations were found in various studies where spinetoram half-life values were reported as 1.29 d in cabbage, 1.95 d in pepper [ 39 ], 2.17 d in pear fruits [ 40 ], 2.6 d in tomato [ 41 ], 4.85 d in cauliflower [ 42 ] and 1.1 d in rice straw [ 16 ]. Faster dissipation of spinetoram from the plant surface may also be attributed to volatilization of the insecticide from the crop surface [ 41 ].…”
Section: Discussionsupporting
confidence: 90%